Geology controls streamflow dynamics - Carlier, Claire; Wirth, Stefanie; Cochand, Fabien; Hunkeler, Daniel; Brunner, Philip (My University, 2018)
Relating stream dynamics to catchment properties is essential to anticipate the influence of changing environ-mental conditions and to predict flows of ungauged rivers. Although the importance of subsurface processes incatchment hydrology is widely acknowledged, geological characteristics are rarely explicitly included in studiesassessing physiographic controls on catchment dynamics. In this investigation of 22 catchments of the SwissPlateau and Prealpes, we use a simple linear regression approach to analyze the relationship between streamflowindicators and various geological and hydrogeological properties of the bedrock and quaternary deposits, alongwith meteorological, soil, land use and topographical characteristics. We use long-term discharge percentiles, aswell as dimensionless flow duration curves (FDC, standardized by long-term mean discharge) that allow toevaluate the catchment response to climate forcing. While climate conditions dominate the high to mediumdischarge percentiles (Q5–Q50), the capacity of the catchments to buffer the meteorological forcing can only beattributed to geological characteristics. The sandstone proportion in the catchments explains 54% of the varianceof both extremities of the dimensionless FDC (Q5/Qmean and Q95/Qmean) and productive quaternary depositsare responsible of 55% resp. 58% of the variance of the two ratios. Examining the hydrogeological characteristicsof both bedrock and quaternary lithologies considerably improves the understanding of catchment dynamics.
Keywords: Streamflow dynamics; Catchment classification; Geology; Hdrogeology properties; Bedroch